STRATEGI RETENSI KARYAWAN BERBASIS EMPLOYEE ENGAGEMENT - Itot Bian Raharjo; Muhammad Fatkhurohman Albashori; Anik Widiyanti; Wahyudiyono Wahyudiyono; Suliantoro Suliantoro (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to determine employee engagement-based employee retention strategies. This research approach collects data through literature studies, which involve reading literature from various sources including books, reports, articles, and journals using qualitative and deductive approaches. The findings in this study are that there are several employee engagement-based employee retention strategies, including empowering leadership, open and transparent communication, career development, recognition and appreciation, work-life balance, positive social and cultural involvement, and involvement in decision making. These strategies are not only able to reduce employee turnover, but also improve overall company performance.